Chinese Mongolian horses may retain early domestic male genetic lineages yet to be discovered. (9th May 2019) - Han, H.; Wallner, B.; Rigler, D.; MacHugh, D. E.; Manglai, D.; Hill, E. W.
Summary: The Mongolian horse represents one of the most ancient extant horse populations. In this study we determined the male‐specific region of the Y chromosome (MSY) haplotype distribution in 60 Chinese Mongolian horses representing five distinct populations. Cosmopolitan male lineages were predominant in horses from one improved (Sanhe), one Chinese Mongolian subtype (Baicha Iron Hoof) and one indigenous (Abaga Black) population. In contrast, autochthonous Y chromosome diversity was evident among the two landrace populations (Wushen and Wuzhumuqin), as the majority of their MSY haplotypes were situated at root nodes in a network. Our results also suggest gene flow between Chinese Mongolian and Arabian horses, as an appreciable number of Wuzhumuqin horses carried haplotypes that are typically observed in Arabian horses. Although most horses carried modern haplotypes as a direct result of recent breed improvement, authentic Chinese Mongolian horses retain an ancient signature of paternal lineages that has not previously been described in extant horse populations. Therefore, further characterization of MSY variation in these populations will be important for the discovery of lost diversity in modern domestic horses and also for understanding the evolutionary history of equine paternal lineages.